1995
DOI: 10.1111/j.1439-0523.1995.tb00859.x
|View full text |Cite
|
Sign up to set email alerts
|

Attempts to overcome postfertilization barrier in interspecific crosses of the genus Lens

Abstract: Wild relatives are a potential source of genetic diversity to lentil {Lens culinaris Medik). The objective of this research was to obtain viable interspecific hybrids between the domesticated lentil and its wild relatives.The paper details the results of a number of interspecific crosses among L. culinaris, L. orientalis, L. odemensis, L. ervoides and L. nigricans. Viable hybrids were produced between L. culinaris x L. orientalis, L. culinaris x L. nigricans, L. culinaris x L. ervoides and between L. culinaris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 11 publications
0
25
2
Order By: Relevance
“…tomentosus × L. lamottei (van Oss et al 1997 ), and L. culinaris ssp. odemensis × L. ervoides ) though viable hybrids have been reported between cultivated species and L. ervoides , L. odemensis , and L. nigricans with the use of GA3 (Ahmad et al 1995 ). reported a high correlation between crossing success and phenotypic similarity based on pollen morphology and in vitro pollen length together with pistil and style length, indicating good predictor of hybridization success between different species.…”
Section: Use Of Cross-compatibility Between Wild and Cultivated Speciesmentioning
confidence: 93%
See 3 more Smart Citations
“…tomentosus × L. lamottei (van Oss et al 1997 ), and L. culinaris ssp. odemensis × L. ervoides ) though viable hybrids have been reported between cultivated species and L. ervoides , L. odemensis , and L. nigricans with the use of GA3 (Ahmad et al 1995 ). reported a high correlation between crossing success and phenotypic similarity based on pollen morphology and in vitro pollen length together with pistil and style length, indicating good predictor of hybridization success between different species.…”
Section: Use Of Cross-compatibility Between Wild and Cultivated Speciesmentioning
confidence: 93%
“…A two-step in vitro method of embryo-ovule rescue was developed to obtain successful distant hybrids by crossing the cultivated lentil with L. ervoides and L. nigricans (Cohen et al 1984 ). However, the same technique used by other workers could not produce the hybrids (Ahmad et al 1995 ;Gupta and Sharma 2005 ). Another study reported development of different protocol , which could be able to rescue the hybrid ovules 18 days after pollination.…”
Section: Embryo Rescuementioning
confidence: 96%
See 2 more Smart Citations
“…The only wild species that can be intercrossed with cultivated lentil easily is L. orientalis, the progenitor of cultivated lentil (Ladizinsky 1979(Ladizinsky , 1993. A recent report showed that viable hybrids could be obtained from the crosses between the cultivated and four wild lentil species by applying gibberellic acid (GA 3 ) after pollination (Ahmad et al 1995). Upon improvement, this technique may lead to an efficient method to transfer useful resistance genes from these wild species into cultivated species.…”
Section: Using Wild Relativesmentioning
confidence: 99%